Blurring Context and One-Sided: Kompas.com in Framing the West Papua Crisis - Adiprasetio, Justito; Taqiyya, Almas (Jurnal Kajian Jurnalisme, 2023)
In September 2021, the conflict between West Papuan separatist groups and the Indonesian National Army (TNI) heated up. Kompas.com, one of Indonesia's media with the most extensive readership, contributes significantly to public understanding and perception of the West Papua crisis. This study aims to examine how Kompas.com frames the West Papua crisis on 7-30 September 2021. Framing analysis examines three important aspects of news framing: crisis frames, thematic and episodic frames, and news sources. The news regarding the West Papua crisis on 7-30 September 2020 was only filled with three frames: conflict, attribution of responsibility, and human interest. Kompas.com has tried to provide space for parties with a moderate position in the conflict, such as the Indonesian Medical Association (IDI), Komnas HAM (National Commission on Human Rights), and Kontras (The Commission for Disappeared and Victims of Violence). However, in general, the news is still very much dominated by news sources from the Indonesian government and the military and not using enough thematic frames. Kompas.com needs to be more comprehensive to report on the crisis in West Papua during the reporting period of 7-30 September 2020. Kompas.com also does not elaborate that the Free Papua movement is plural and fragmentary, with a spectrum of violent movements to peace movements. The conclusion of this study, Kompas.com tends to blur the context of the West Papua crisis, which risks limiting and directing public understanding of the West Papua crisis to exist within the government's frame.